Land Use in Australia Past, Present and Future - Thackway, Richard (ANU Press, 2018)
Land Use in Australia: Past, Present and Future, is a compilation of invited chapters from Australia's leading specialists in land use policy and planning and land management. Chapters present many widely recognised issues involved in Australia's land use policy and planning, including limited understanding and poor awareness of: the rich history of poor decisions on land use planning and management across different levels of government the discontinuities between providers of national biophysical information the tools, data and information to improve national land use decision-making outcomes the poor synthesis and integration between science to policy to natural resource management and resource condition the benefits of land use practitioners engaging in connection, cooperation, mutual inquiry and collective social learnings. The aims of the book are threefold: 1) provide a review of the current status of land use policy and planning in Australia; 2) provide a resource to inform and influence the development of land use policy and planning; and 3) provide a sound contribution to Australia's public-private land use debates in the future. The audience for the book includes government and non-government land management agencies from state and national bodies, universities and researchers.